Evaluation of the “Eat Better Feel Better” Cooking Programme to Tackle Barriers to Healthy Eating - Garcia, Ada L. (Int J Environ Res Public Health, 2017)
We evaluated a 6-week community-based cooking programme, “Eat Better Feel Better”, aimed at tackling barriers to cooking and healthy eating using a single-group repeated measures design. 117 participants enrolled, 62 completed baseline and post-intervention questionnaires, and 17 completed these and a 3–4 months follow-up questionnaire. Most participants were female, >45 years, and socioeconomically deprived. Confidence constructs changed positively from baseline to post-intervention (medians, scale 1 “not confident” to 7 “very confident”): “cooking using raw ingredients” (4, 6 p < 0.003), “following simple recipe” (5, 6 p = 0.003), “planning meals before shopping” (4, 5 p = <0.001), “shopping on a budget (4, 5 p = 0.044), “shopping healthier food” (4, 5 p = 0.007), “cooking new foods” (3, 5 p < 0.001), “cooking healthier foods” (4, 5 p = 0.001), “storing foods safely” (5, 6 p = 0.002); “using leftovers” (4, 5 p = 0.002), “cooking raw chicken” (5, 6 p = 0.021), and “reading food labels” (4, 5 p < 0.001). “Microwaving ready-meals” decreased 46% to 39% (p = 0.132). “Preparing meals from scratch” increased 48% to 59% (p = 0.071). Knowledge about correct portion sizes increased 47% to 74% (p = 0.002). Spending on ready-meals/week decreased. Follow-up telephone interviewees (n = 42) reported developing healthier eating patterns, spending less money/wasting less food, and preparing more meals/snacks from raw ingredients. The programme had positive effects on participants’ cooking skills confidence, helped manage time, and reduced barriers of cost, waste, and knowledge.